Evaluation of the effect of chlorhexidine and sodium hypochlorite in adhesive cementation of fiber posts - in vitro study - Tainara CONTE; Guilherme Schmitt de ANDRADE; Ana Paula GADONSKI; Daniella Cristo SANTIN; Fabiana Scarparo NAUFEL (Universidade Estadual Paulista, 2019)
Abstract Introduction The attachment of fiberglass posts is achieved through an adhesive process. Failures in adhesion may occur due to the hydrolytic degradation of the adhesives, or to the degradation of the collagen fibres of the hybrid layer by intrinsic enzymes. Objective To evaluate the effect of chlorhexidine and sodium hypochlorite treatment on bond strength to dentin. Material and method Thirty bovine roots were randomly distributed into 3 groups (n=10): a) Control, b) 2% Chlorhexidine, and c) 5% Sodium Hypochlorite. Next, RelyX® ARC resin cement was used to cement the post. Each specimen resulted in samples from the three root thirds that were submitted to the pushout test (MPa) at 24 hours and 12 months. Bond strength values were analysed using the Kolmogorov-Smirnov, 3-way ANOVA and Tukey tests. The fracture mode of the pin was also analysed using stereomicroscopy. Result There were no significant differences between treatments at the immediate time (p=0.0644) or in the interaction of factors (p=0.1935). After one year, the experimental groups showed no significant differences in bond strength in relation to the control group, with the exception of the cervical third of the chlorohexidine group in which there was a significant loss of adhesion. As for the fracture mode, there was a predominance of the mixed type in all groups and thirds. Conclusion The use of chlorhexidine or hypochlorite provides neither benefits nor losses in the adhesive bond strength of fiberglass posts. However, there is an influence of the root thirds, with the worst bond strength in the apical third.